After Race : Racism After Multiculturalism - Darder, Antonia (Book collections on Project MUSE., 2004)
After Race pushes us beyond the old "race vs. class" debates to delve deeper into the structural conditions that spawn racism. Darder and Torres place the study of racism forthrightly within the context of contemporary capitalism. While agreeing with those who have argued that the concept of "race" does not have biological validity, they go further to insist that the concept also holds little political, symbolic, or descriptive value when employed in social science and policy research. Darder and Torres argue for the need to jettison the concept of "race," while calling adamantly for the critical study of racism. They maintain that an understanding of structural class inequality is fundamentally germane to comprehending the growing significance of racism in capitalist America.